Territorial Energy Vulnerability Assessment to Enhance Just Energy Transition of Cities - Calvo, Rubén; Amigo, Catalina; Billi, Marco; Fleischmann, Matías; Urquiza, Anahí; Álamos, Nicolás; Navea, José (Frontiers in Sustainable Cities, 2021)
Energy poverty is a crucial concept in current global energy policy, both for the importance of securing equitable access to high-quality energy services to all human populations and to advance towards a just energy transition to a decarbonized economy. Nonetheless, one of the limitations of this concept due to its focus at the household scale, it has tended to omit relevant energy conditions at a territorial scale, which can also be a dimension of significant deprivation (e.g., transportation, schools, hospitals, public services, industrial uses among others.). On the other hand, energy services are highly dependent on context: on the geographic, ecological, technical, economic, and sociocultural conditions. This context-dependency determines the range of energy and technological alternatives available in a territory. Hence, a conceptual framework is required to better understand the starting point to a just energy transition, capable of integrating the complexity of socio-techno-ecological systems. To fill this gap, we present a framework based on the concept of Territorial Energy Vulnerability, defined as the propensity of a territory to not guarantee equitable access - in quantity and quality - to resilient energy services that allow the sustainable human and economic development of its population. That is a greater probability of gaps in access or inequity in quality energy services or significant impacts derived from socio-natural risks that make it incapable of guaranteeing a sustainable and resilient provision of these services. Built on state-of-the-art conceptualizations of risk, we develop an indicator-based framework on vulnerability understood as the combination of sensitivity and resilience characteristics of socio-techno-ecological systems. Sensitivity relates to economic, demographic, infrastructure, technology, culture, and knowledge characteristics of socio-techno-ecological components. Meanwhile, resilience is presented in a three-dimensional framework based on flexibility, register, and self-transformation capacity of socio-techno-ecological systems. An application of this framework is developed using three case studies: Arica, Los Andes and Coyhaique, all Chilean cities with diverse ecological, technical, economic, and sociocultural conditions that shape territorial vulnerability. Using this framework as a diagnostic tool, the development of a just energy transition could adapt existing concepts of energy poverty and decarbonization pathways into context-specific guidelines and policies.